Analisis Manajemen Logistik Obat Dalam Perencanaan Pengendalian Safety Stock Di Instalasi Farmasi Rumah Sakit - Simamora, Harmoni; Komara, Endang; Hidayat, Dasrun (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Drug logistics management is one of the efforts to improve the degree of health. The most important aspect of drug logistics management by optimizing the use of drugs, this should include planning to ensure the availability, safety and effectiveness of drug use. The availability of drugs is currently a demand for health services. Drug logistics management in hospital pharmacy installations which includes stages, namely planning, procurement, receipt and storage, distribution, control, and destruction, which are interrelated with each other, so they must be well coordinated so that each can function optimally. This study aims to analyze drug logistics management in planning, controlling safety stock in pharmaceutical installations. This study used qualitative research with a descriptive approach through unstructured in-depth interview techniques. The data used is primary data in the form of direct interview results. The informants in this study were the head of the pharmaceutical installation, the head of the drug logistics warehouse and the head of the inpatient pharmacy. Research shows that in planning, safety stock control has gone well. Planning uses consumption methods, feeding patterns and prescribing patterns while to control drug safety stock applies an additional 10% to its procurement from drug consumption in the previous period, records drug stock cards, pays attention to slow-moving, fast-moving drugs and always pays attention to drug expiration dates. The destruction of drugs has been going on as it should, but the hospital does not yet have a means of drug destruction.